Lecturers’ Practices in Using AI-Powered Tools to Support Academic Writing in EFL Classrooms - Hadijah; Hariadi Syam; Nurdin Noni (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
Artificial intelligence (AI) has increasingly influenced academic writing instruction in English as a Foreign Language (EFL) classrooms. This study aims to explore lecturers’ practices in using AI-powered tools to support academic writing, with attention to their pedagogical use, stages of integration, instructional roles, and perceived challenges. This study employed a qualitative design involving ten lecturers from two Indonesian universities. Data were collected through semi-structured interviews and document analysis and were analyzed using thematic analysis. The findings show that AI-powered tools, including Grammarly, QuillBot, and ChatGPT, are mainly used for grammar correction, paraphrasing, vocabulary improvement, and idea generation. The use of these tools is mostly directed toward the revision stage, while planning and drafting remain largely student-driven. Lecturers play an important role in controlling and guiding AI use to maintain students’ authorship and academic integrity. However, AI integration is still limited by lecturers’ digital competence, lack of institutional training, unclear guidelines, and concerns about student dependency on automated outputs. The study implies that responsible AI integration in EFL academic writing requires clear institutional guidelines, lecturer training, and ethical writing policies.